Pathogenesis and Novel Therapeutics in Asthma - Bazan-Socha, Stanislawa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Asthma is a prevalent chronic inflammatory disease of the airways with complex etiology and mechanistic pathways and variable clinical presentation. Such heterogeneity renders the search for targeted therapies difficult. Currently, the best-known disease phenotype with tailored biological treatment is eosinophilic asthma; however, even in some of these patients, anti-IL5 treatment is ineffective. Furthermore, about a quarter of patients, especially those with a severe phenotype, develop progressive and irreversible airway obstruction, leading to persistent symptoms despite optimized treatment. Therefore, new therapeutic approaches are still needed, particularly in severe asthma. The Special Issue presents asthma research focusing on modern personalized therapeutic approaches. Particular interest is directed to novel asthma biomarkers, including molecular and epigenetic ones, shining new light on pathogenesis, phenotyping, and customized therapy in various airway inflammatory patterns of the disease. In addition, research articles on airway epithelial cell dysfunction, airway remodeling, and the overlap between asthma and chronic obstructive pulmonary disease are welcomed. Stanislawa Bazan-Socha (Guest Editors)